The distinction between real and apparent emotion in pretend play and deception situations - Sidera,Francesc (2008)
Childrens understanding of the distinction between real and apparent emotion was assessed using a deception task and a pretend play task. In each task, children aged from 5 to 7 listened to a story and were asked about protagonists external and internal emotion. Our procedure allowed children to show their understanding of the distinction spontaneously, with prompting and after explicit questioning. Children had great difficulty to make the distinction spontaneously in both tasks. However, they performed better when they were explicitly asked whether protagonists external and internal emotion could be different. Globally, 7 year-olds understood the distinction better than 5 year-olds. More important, we found no differences between the deception and the pretend play tasks. A possible explanation is that childrens understanding of the distinction develops simultaneously in both kinds of situations. The importance of understanding emotions in pretend play for the comprehension of the distinction between real and apparent emotion is discussed.